Constraining the degree of the dominant mode in QQ Vir - Baran, Andrzej; Telting, John; Ostensen, Roy; Winiarski, Maciej; Drozdz, Marek; Koziel, Dorota; Reed, Mike; Oreiro, Raquel; Silvotti, Roberto; Siwak, Michal; Heber, Ulrich; Papics, Peter (Astrophysics and Space Science, 2010)
We present early results of the application of a method which uses multicolor photometry and spectroscopy for a"" discrimination. This method has been successfully applied to the pulsating hot subdwarf Balloon 090100001. Here we apply the method to QQ Vir (PG1325+101). This star was observed spectroscopically and photometrically in 2008. Details on spectroscopy can be found in Telting et al. (Astrophys. Space Sci. 2010, this volume), while photometry and preliminary results on a"" discrimination are provided here. The main aim of this work was to compare the value of the a"" parameter derived for the main mode in QQ Vir to previously published values derived by using different methods.
Keywords: Hot subdwarfs; Pulsating stars